The effect of introducing Basic Antenatal Care Plus and Umbiflow on antenatal care and perinatal mortality - Pattinson, Robert Clive (University of Pretoria, 2022)
Thesis (PhD (Obstetrics and Gynaecology))--University of Pretoria, 2022.